Seasonal Modulation of Dissolved Oxygen in the Equatorial Pacific by Tropical Instability Vortices. Issue 11 (22nd November 2021) - Eddebbar, Y. A.; Subramanian, A. C.; Whitt, D. B.; Long, M. C.; Verdy, A.; Mazloff, M. R.; Merrifield, M. A.
Abstract: Tropical instability vortices (TIVs) have a major influence on the physics and biogeochemistry of the equatorial Pacific. Using an eddy‐resolving configuration of the Community Earth System Model (CESM‐HR) and Lagrangian particle tracking, we examine TIV impacts on the three‐dimensional structure and variability of dissolved oxygen (O2 ) in the upper equatorial Pacific water column. In CESM‐HR, the simulated generation and westward propagation of TIVs from boreal summer through winter lead to the seasonal oxygenation of the upper northern equatorial Pacific, exhibited as a deepening of hypoxic depth west of 120°W. TIV effects on the equatorial Pacific oxygen balance are dominated by eddy‐advection and mixing, while indirect TIV effects on O2 consumption play minor roles. These advective effects reflect the transient displacements of isopycnals by eddy pumping as well as vortex transport of oxygen by eddy trapping, stirring, and subduction. TIVs influence on the upper equatorial Pacific O2 distribution and variability has important implications for understanding and modeling marine ecosystem dynamics and habitats, and should be taken into consideration in designing observation networks in this region. Plain Language Summary: Tropical instability vortices (TIVs) are eddies that stir and transport water masses in the equatorial Pacific. From summer through winter, vortices are generated in the eastern equatorial Pacific and propagate toward the west, causing major physical and biogeochemical changes in the upper equatorial Pacific. We examine their effects on oxygen distributions and variability in the equatorial Pacific using a global model of ocean circulation and biogeochemistry. From boreal summer through winter, TIVs oxygenate the upper ocean through a series of processes, namely their influence on upper ocean density layers and lateral and vertical water mass exchanges that lead to a temporary deepening of the oxygen minimum zones and an expansion of vertical habitable space along their paths. Our analysis demonstrates that TIVs comprise an important mechanism regulating simulated oxygen distributions in the equatorial Pacific; these important phenomena should be explored in observational campaigns and their effects should be considered in the context of improving climate models. Key Points: Tropical instability vortices (TIVs) oxygenate the northern upper equatorial Pacific TIVs seasonality modulates the oxygen minimum zone structure and seasonal variability of ecosystem habitable space in the equatorial Pacific TIVs' oxygenation effects are dominated by eddy advective effects while biogeochemical feedbacks play a minor role